Comparison of nitrous oxide/midazolam and nitrous oxide/promethazine for pediatric dental sedation: A randomized, cross-over, clinical trial - Sedigheh Mozafar; Majid Bargrizan; Mojtaba Vahid Golpayegani; Shahnaz Shayeghi; Rahil Ahmadi (Wolters Kluwer Medknow Publications, 2018)
Background: This study compared the safety and efficacy of nitrous oxide (N2O)/midazolam and N2O/promethazine for dental treatment of uncooperative children. Materials and Methods: In this randomized, cross-over, clinical trial investigation Eighteen healthy uncooperative children with a pair of similar teeth requiring the same treatment were included.Combination of N2O/midazolam was given in one visit, where N2O/promethazine was administrated in the other appointment for each patient in a cross-over manner. Oxygen saturation and heart rate as well as behavior parameters according to Houpt behavior scales were recorded. Postoperatively, patients' anxiety and parents' satisfaction were assessed by visual analog score and a questionnaire, respectively. Data were analyzed using Wilcoxon' s signed rank test and Paired t-tests with a P value set at 0.05. Results: Physiologic parameters were within normal limit in both groups. Children in midazolam group were significantly deeper sedated compared to other groups. In the first phase, children sedated with midazolam behaved superiorly in comparison to promethazine, while there was no difference at the final phase of the treatment between the two groups. Conclusion: Both of the drug combinations resulted in acceptable, efficient, and safe sedation outcomes.